SOLAR POWERED DRINKING WATER SUPPLY BUSINESS MODEL SUSTAINABLE IN IMPROVING QUALITY COMMUNITY LIFE - Bambang Susanto; Erna Garnia; Kusmadi Kusmadi; Muhammad Fauzan; Siti Riyyan Lisaumi (LPPM STIE Muhammadiah Bandung, 2026)
The condition of densely populated areas, suburbs and 3T areas (underdeveloped, outermost, frontier) have gaps in meeting primary needs such as drinking water which is the most important human need. Objectives: Density of population and limited land for PDAM water pipelines are not accessible and are still often constrained. This includes water conditions in densely populated urban areas and urban suburbs that are not covered by PDAMs and 3T areas which are completely unreachable by clean water providers so that the water produced is polluted with household waste, groundwater exploitation and the high rate of population growth and migration to urban areas. Methodology: The research method is quantitative and qualitative methods. Qualitative information obtained from respondents related to preliminary research that is generalization of the object under study. Finding: The problem is still considered a local problem so that the solution is never complete and the concerns of people in densely populated urban areas perceive PDAM as a provider of drinking water using chemicals that have an impact on body condition compared to healthy drinking water sources originating from the soil. Conclusion: From these problems, one of the solutions is to create a source of drinking water in densely populated urban areas by utilizing solar energy for communities around densely populated urban areas, as well as for 3T communities where there is no energy source.